Features of water crystallization - V. Yu. Stetsenko (Литьë и металлургия)
Water is mainly composed of ice nanocrystals. The peculiarities of water crystallization can be explained on the basis of its nanostructural structure and nanostructural crystallization. Atmospheric air molecules dissolve well in water and are adsorbed by its nanocrystals. It is shown that the amount of expansion of ice, when water solidifies, is proportional to the concentration of air dissolved in it. The concentration of air dissolved in water decreases significantly with an increase in its temperature. Hot water solidifies faster than cold water because there is less air concentration in hot water. Its bubbles, released on ice crystals, reduce the rate of crystallization of water. A large supercooling of water occurs as a result of the blocking action of adsorbed air, which prevents the unification of ice nanocrystals into crystallization centers. Shaking a bottle of supercooled water leads to desorption of air and accelerated crystallization of water. Air bubbles released on dendritic ice crystals reduce the degree of branching of these crystals. It has been shown that music increases the intensity of removal of gas bubbles and is able to influence the shape of dendritic ice crystals during water crystallization. It has been shown that an increase in the volume of sound and (or) a decrease in its frequency increase the intensity of removal of air bubbles from dendritic ice crystals and increase the branching of these crystals.